The effects of multiple representation method and prior knowledge level on problem solving skills and cognitive load - SATICI, AHMET FEYZİ (My University, 2023)
In this study, the effect of multiple representation method and prior knowledge level in solving ill-structured problems was investigated. Quasi-experimental and 2x2 (multiple representation method x prior knowledge level) factorial designs were used in the study. The study group consists of 39 undergraduate students. The dependent variables of the study were determined as problem solving skills, cognitive load, and permanence. The independent variables were considered as multiple representation method (step-by-step, holistic) and prior knowledge levels (novice, expert). Prior knowledge level test, problem solving skills test and cognitive load scale developed to measure the variables were used as data collection tools within the scope of the study. The data was analysed with two-way analysis of variance and independent groups t-test as the data obtained from the data collection tools exhibited normal distribution. In the results that were significant in the analysis, Cohen (d) in the independent groups t-tests and eta-square (η2) in the two-way analysis of variance were also shown. As a result of the research, it is evident that the level of prior knowledge and the interaction (interaction effect) of the level of prior knowledge and the multiple representation method affect problem solving skills. In addition, it was concluded that the interaction of multiple representation method and prior knowledge level was statistically significant in terms of cognitive load variable. The findings supported the expertise reversal effect.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sosyoloji; Eğitim; Social Sciences and Humanities; Psychology; Developmental Psychology; Sociology; Education; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ, GELİŞTİRME; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, DEVELOPMENTAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Gelişim ve Eğitim Psikolojisi; Social Sciences & Humanities; Developmental and Educational Psychology; Cognitive load; Illdefined problems; Multiple representation; Prior knowledge; Problem solving; Worked examples